2022
DOI: 10.1186/s12943-022-01591-z
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding RNAs related to the hedgehog pathway in cancer: clinical implications and future perspectives

Abstract: Cancer is a type of malignant affliction threatening human health worldwide; however, the molecular mechanism of cancer pathogenesis remains to be elusive. The oncogenic hedgehog (Hh) pathway is a highly evolutionarily conserved signaling pathway in which the hedgehog-Patched complex is internalized to cellular lysosomes for degradation, resulting in the release of Smoothened inhibition and producing downstream intracellular signals. Noncoding RNAs (ncRNAs) with diversified regulatory functions have the potenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 171 publications
0
3
1
Order By: Relevance
“…The results of qPCR and western blotting had showed that PUR could upregulate the Shh, SMO, and Gli1 expression, which suggested that PUR indeed activated the Hedgehog signaling pathway. Many studies had shown that activation of the Hedgehog signaling pathway could accelerate the progression of various tumors, and blocking this pathway was a new strategy for the treatment of tumors [38][39][40][41]. PUR-induced activation of Hedgehog signaling pathway could not promote the malignant characteristics of cervical cancer cells in our studies, which seemed to contradict previous researches.…”
Section: Biomed Research Internationalcontrasting
confidence: 85%
“…The results of qPCR and western blotting had showed that PUR could upregulate the Shh, SMO, and Gli1 expression, which suggested that PUR indeed activated the Hedgehog signaling pathway. Many studies had shown that activation of the Hedgehog signaling pathway could accelerate the progression of various tumors, and blocking this pathway was a new strategy for the treatment of tumors [38][39][40][41]. PUR-induced activation of Hedgehog signaling pathway could not promote the malignant characteristics of cervical cancer cells in our studies, which seemed to contradict previous researches.…”
Section: Biomed Research Internationalcontrasting
confidence: 85%
“…Previous studies, including the present study, have demonstrated the essential role of the Hedgehog cascade, particularly its executor GLI1, in cancer stem cell-mediated NSCLC development and progression [16][17][18]. The Hedgehog cascade can be stimulated in a canonical way, dependent on the translocation of its upstream regulator SMO, or in an uncanonical way, dependent on the expression of aberrant non-coding RNAs [19,20]. lncRNAs function at the epigenetic, transcription, and posttranscription levels in either a transor cis-manner [21].…”
Section: Introductionmentioning
confidence: 52%
“…It is estimated that one-third of malignancies are correlated with abnormal activity of the Hh signaling pathway [ 70 ]. Dysregulation of Hh signaling can contribute to the imitation, growth, metastasis, and apoptosis of several types of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, three patterns of induction of the Hh signaling cascade have been identified in several cancers. These patterns are ligand independent oncogenic Hh pathway, autocrine or juxtacrine and paracrine or reverse paracrine patterns [ 70 ].…”
Section: Discussionmentioning
confidence: 99%